Qualidade de sementes de soja resfriadas artificialmente - Demito, Angélica (2006)
The objective of this research was to artificial chill of soybean seeds before bagging, through out the insuflation of cold air produced by a PSC 40 COOLSEED, measure the thermal stability over a period of time and, periodically evaluate the vigor, germination in the two blocks and to carry on a laboratory experiment with seeds from the same variety by measuring vigor and germination of the seed kept at controlled temperatures. This project was developed at the Seed Improvement Unit of the Agro Santa Rosa S.A.E.C.A. Company, located in the municipality of Hernandarias, Paraguay, . Soybean seeds variety BRS184 were artificially cooled in 100-ton wood silo. After chilling the seeds were immediately bagged in polypropylene sacks with an initial temperature ranging from 12-15 C and kept packed in a conventional seed storage facility. Temperature sensors were introduced at several depths (50, 100, 150 and 200 cm) in the seed block in order to monitor the thermal stability . A block of seeds from the same variety without been cold treated, was packed inside the same storage facility with digital temperature sensors introduced at depths of 50, 100, 150 and 200 cm as a control. Each seed block was composed of 840 polypropylene bags, stored close to each other inside the same conventional non-air conditioned seed storage facility. The initial germination of the chilled seed was 82,0% and the final after 140 days in storage was 81,0%, above the level of 80,0% that is the minimum percentage of germination for soybean seeds to be market as seed. The cold treatment helped to maintain seed germination. On the untreated seed block the initial germination was also 82,0% but by the of the same storage time 69,0% well below the standard necessary to be considered seed. At the same time, an experiment was conducted in the laboratory of UNIOESTE (Universidade do Oeste do Parana), Cascavel Campus, State of Parana, utilizing seed samples collected from the bags that were cold treated. These samples were maintained in a chamber at temperatures similar to those indicated by the thermometers installed in the seed blocks. The temperatures of the chamber were updated weekly to reflect the conditions of the seed in the block. The initial moisture content of the soybean seed kept at room temperature was 11,0% and the final was 10,2%. And 9,2% for the seeds keep at artificialy cooling. The thermal stability of the seed chilled before bagging was considered satisfactory, because their temperature was kept in a range adequate for maintaining seed quality during the storage period. Results from the seeds planted on the field showed the beneficial of the cold treatment because the germination was 80% while the untreated seed was 69%.